Gambaran Sanitasi Dasar dengan Kejadian Diare di Kawasan Risiko Banjir - Dea Ananda Br.SK; Nur Asiyah Siregar; Rahmah Fadlilatu Syahadah; Akmal Fiqhi Ranu Mahendra; Ananda Nurmairani Laoli; Putra Apriadi Siregar (Lembaga Pengembangan Kinerja Dosen, 2023)
Floods can contaminate water sources and damage sanitation systems, including drinking water systems and basic sanitation facilities such as sewers. If hygiene is compromised, the risk of disease transmission, including diarrhea, can increase significantly. The purpose of this study was to determine the relationship between hygiene status and the incidence of diarrhea in Pasar 3 Tembung Village, Percut Sei Tuan District, Deli Serdang District. This type of research is a research method with a qualitative descriptive research approach, where data collection techniques include observation, interviews and documentation. The conclusion of this study is that flooding can be an important risk factor that increases the incidence of diarrheal disease. Floods often disrupt waterways and sanitation systems, increasing drinking water and environmental pollution. Pollution of water and food waste can cause the spread of diseases such as diarrhea in the community